Understanding the gnawing threat of encroachment of urban green spaces in Ghana’s growing urban fabric - Benjamin Doe; Prince Aboagye Anokye; Ama Kyerewaa Attakorah; Stephen Biliyitorb Liwur (Discover Cities)
Abstract Urban green spaces offer unique social, health, and economic benefits such as sanitizing the air, protecting flora and fauna, and reducing heat waves, ultimately improving life quality. However, despite the several benefits associated with these spaces, they are threatened with rapid depletion. The study assessed the encroachment of urban green spaces by case-studying Asokwa Municipality employing qualitative research methods and spatial analysis using GIS tools. Following this, urban green spaces have over the span of 20 years declined substantially from 49 to 16%. Even though the urban green space-population ratio is close to ideal based on the WHO’s recommendations of 1:50 m2, about 70% of the green spaces have been encroached upon by urban development. These encroachments are a result of poverty and poor integration of the informal economic operators in the urban space. Further assessment showed that the massive deteriorations of these urban green spaces are strongly linked to weak coordination between traditional authorities, who are custodians of the city’s land, and planning officers, who superintend spatial planning activities in the city. To address this, the researchers recommend that city authorities consider public–private partnerships to safeguard urban green spaces. Specifically, converting existing green spaces into green parks for leisure purposes can enhance socialization while preserving ecological character. Also, introducing user rights in management can serve as an environmental change catalyst to prevent encroachment.